The Effectiveness of Metacognitive Strategy on Students’ Reading Comprehension of Narrative Text - Solekah, Ratna Nur; Imam Nur Aziz (JEET, Journal of English Education and Technology, 2024)
Reading is something that is very needed in our lives. By reading we will open the window of the world and if we can take wisdom from what we read, we will become a great and noble human being as exemplified by the Prophet Muhammad. This study aims to determine whether there is a significant influence using metacognitive strategies for students’ reading comprehension in narrative texts. This study used a t-test experiment involving each individual in Grade VIII of SMP NU Panunggalan consisting of 34 students. The results showed that the mean score of the pre-test yielded 40.2941 and the average post-test post-test yielded 92.3529. The mean deviation produces a value of 52.05882, standard deviation produces a value of 21.85065 and produces a t-test of 13.892. T-table 5 % shows the number 2.032 and t-table 1% shows the number 2.738. Then it can be concluded that 2.032<13.892>2.738. These results show significant results from the experiments on the effectiveness of metacognitive strategies on students’ reading comprehension in narrative texts.